Use of Specialty Soy Products to Replace Poultry Meal and Spray-Dried Blood Plasma in Diets Provided to Nursery Pigs Housed in Commercial Conditions - Ethan B. Stas; Jamil E. G. Faccin; Zach B. Post; Chad W. Hastad; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,260 pigs (PIC TR4 × [Fast LW × PIC L02]; initially 14.8 lb) were used to evaluate a specialty soy protein source as an alternative to poultry meal and spray-dried blood plasma on nursery pig performance in a commercial environment. At weaning, pigs were allotted to 1 of 5 dietary treatments based on initial weight in two research nurseries. In the first facility there were 20 pigs per pen and 10 pens per treatment. In the second facility, there were 21 pigs per pen and 12 replications per treatment for a total of 22 replications per treatment. Dietary treatments included a control diet containing 9.5% poultry meal (AV-E Digest, XFE Products, Des Moines, IA) and 4.13 (phase 1) or 2.75% (phase 2) spray-dried blood plasma (Appetein, APC Inc., Ankeny, IA). The four additional diets were set up in a 2 × 2 factorial with a novel soy protein concentrate (AX3 Digest; Protekta; Plainfield, IN) or fermented soybean meal (MEPro; Prairie Aquatech; Brookings, SD) replacing poultry meal or poultry meal and spray-dried blood plasma in the control diet. Pigs were fed experimental diets during phase 1 (d 0 to 7) and phase 2 (d 7 to 21). Following phase 2, pigs were fed a common diet for an additional 21 d (d 21 to 42). During the experimental period (d 0 to 21), pigs fed the novel soy protein concentrate had improved (P<0.001) F/G with no differences in ADG or ADFI compared to pigs fed fermented soybean meal. During the experimental period (d 0 to 21) and overall (d 0 to 42), pigs fed soy protein as a replacement to poultry meal had increased (P≤ 0.016) ADG and ADFI compared to pigs fed the control diet. During the experimental period (d 0 to 21), pigs fed soy protein as a replacement to spray-dried blood plasma had improved (P= 0.044) F/G compared to pigs fed soy protein without replacing spray-dried blood plasma, with no differences in ADG or ADFI. In summary, utilizing a specialty soy protein source as a replacement for poultry meal improved growth performance. Replacing poultry meal and spray-dried blood plasma with soy protein improved feed efficiency when treatment diets were fed, but not overall. In addition, the novel soy protein concentrate improved feed efficiency compared to fermented soybean meal during the experimental period with no effect on ADG or ADFI.
Keywords: soy products; poultry meal; spray-dried blood plasma; nursery pig